2007
DOI: 10.1176/ajp.2007.164.4.663
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Emergence of Psychotic Disorders in Adolescents With 22q11.2 Deletion Syndrome

Abstract: Genetic, cognitive, and psychiatric risk factors for the evolution of psychotic disorders in 22q11.2 deletion syndrome during adolescence were identified. Early intervention in the subgroup of children with subthreshold signs of psychosis and internalizing symptoms (especially anxiety symptoms) may reduce the risk of developing psychotic disorders during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
150
4
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(174 citation statements)
references
References 34 publications
15
150
4
5
Order By: Relevance
“…Most had a nonpsychotic disorder at baseline (eg, 60.7% had an anxiety disorder). Nine (32.1%) met criteria for a psychotic illness at time 2, including six with schizophrenia or schizoaffective disorder [13]. In contrast to the three cross-sectional studies summarized in the previous section, which had a total sample of 213 mostly adults with 22qDS and found no significant association of the COMT Met allele with psychotic illness [7,19,36], this allele was reported to be associated with the nine patients with psychotic illness in this young cohort [13].…”
Section: Possible Risk and Predictive Factors For Schizophrenia Exprecontrasting
confidence: 54%
See 3 more Smart Citations
“…Most had a nonpsychotic disorder at baseline (eg, 60.7% had an anxiety disorder). Nine (32.1%) met criteria for a psychotic illness at time 2, including six with schizophrenia or schizoaffective disorder [13]. In contrast to the three cross-sectional studies summarized in the previous section, which had a total sample of 213 mostly adults with 22qDS and found no significant association of the COMT Met allele with psychotic illness [7,19,36], this allele was reported to be associated with the nine patients with psychotic illness in this young cohort [13].…”
Section: Possible Risk and Predictive Factors For Schizophrenia Exprecontrasting
confidence: 54%
“…However, there may be some differences in auxiliary clinical features (eg, lower rates of comorbid substance use disorders) [12,13]. Also, some evidence indicates that patients with 22qDS-schizophrenia may have neurobehavioral characteristics other than schizophrenia's core symptoms [14].…”
Section: Clinical Signs and Symptoms Of Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Only one longitudinal study of youth with VCFS has been published. Those findings suggested that at Time 1 (late childhood), subthreshold psychotic symptoms, anxiety (especially OCD) and depression symptoms, and lower verbal IQ scores predicted the onset of psychotic disorders in adolescence 47 . The purpose of the present investigation was to attempt to replicate these data using a larger sample with more neuropsychological and psychiatric dependent variables.…”
Section: Nih Public Accessmentioning
confidence: 97%